The Ubiquitin Proteasome System in Hematological Malignancies: New Insight into Its Functional Role and Therapeutic Options - Di Costanzo, Antonella (Cancers (Basel), 2020)
The ubiquitin proteasome system (UPS) is the main cellular degradation machinery designed for controlling turnover of critical proteins involved in cancer pathogenesis, including hematological malignancies. UPS plays a functional role in regulating turnover of key proteins involved in cell cycle arrest, apoptosis and terminal differentiation. When deregulated, it leads to several disorders, including cancer. Several studies indicate that, in some subtypes of human hematological neoplasms such as multiple myeloma and Burkitt’s lymphoma, abnormalities in the UPS made it an attractive therapeutic target due to pro-cancer activity. In this review, we discuss the aberrant role of UPS evaluating its impact in hematological malignancies. Finally, we also review the most promising therapeutic approaches to target UPS as powerful strategies to improve treatment of blood cancers.